Taking stakes in the unknown : tracing post-black art - Adusei-Poku, Nana (Image (Transcript (Firm)), 2021)
In 2001, Freestyle, a survey exhibition curated by Thelma Golden at the Studio Museum in Harlem, introduced both a young generation of artists of African descent and the ambitious yet knowingly opaque term post-black to a pre 9-11 and pre-Obama world. In Taking Stakes in the Unknown, Nana Adusei-Poku contextualizes the term post-black in its socio-historical and cultural context. Whilst exploring its present legacy and past potential, she examines works by artists who were defined as part of the post-black generation: Mark Bradford, Leslie Hewitt, Mickalene Thomas and Hank Willis Thomas - and, by expanding the scope of the definition, the Black German artist Philip Metz.